PENGARUH SENAM IRAMA TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK RAUDHATUL JANNAH PASAMAN BARAT - Murpida; Indra Yeni; Nurhafizah; Vivi Anggraini (STKIP Subang, 2026)
The purpose of this study was to determine the effect of rhythmic gymnastics on the gross motor development of children aged 5-6 years at Raudhatul Jannah Kindergarten, West Pasaman. This study is based on the results of observations that show that the gross motor development of children at Raudhatul Jannah Kindergarten, West Pasaman has not developed optimally. Most children still have difficulty in carrying out physical activities that involve body movement coordination. This type of research is quantitative research with a quasi-experimental method. The research population was all children at Raudhatul Jannah Kindergarten, West Pasaman. The sampling technique used a purposive sampling technique, namely group B2 was selected as the experimental class and group B3 was selected as the control class with each class consisting of 15 children. Research data were collected through testing, documentation, and observation techniques. Data analysis carried out normality tests, homogeneity tests, and hypothesis tests, then the data were processed with a difference test (t-test). Based on the results of the study, the average pre-test score of the experimental class was 26.8 while the average post-test score of the experimental class was 46.33. Meanwhile, the average pre-test score for the control class was 25.2, and the average post-test score for the control class was 41.47. A t-test was then conducted, with a value of 0.006 below the 0.05 criterion. Thus, there was a significant difference between the experimental and control classes. The results of this study indicate that rhythmic gymnastics activities influence the gross motor development of children aged 5-6 years at Raudhatul Jannah Kindergarten, West Pasaman.